Glucose oxidase as an alternative to antibiotic growth promoters improves the immunity function, antioxidative status, and cecal microbiota environment in white-feathered broilers - Zhao, Wenyu; Huang, Yuan; Cui, Na; Wang, Ruiguo; Xiao, Zhiming; Su, Xiaoou (Frontiers in Microbiology, 2023)
This study aimed to demonstrate the effects of glucose oxidase (GOD) on broilers as a potential antibiotic substitute. A total of four hundred twenty 1-day-old male Cobb500 broilers were randomly assigned into five dietary treatments, each with six replicates (12 chicks per replicate). The treatments included two control groups (a basal diet and a basal diet with 50 mg/kg aureomycin) and three GOD-additive groups involving three different concentrations of GOD. Analysis after the t-test showed that, on day 21, the feed:gain ratio significantly decreased in the 1,200 U/kg GOD-supplied group (GOD1200) compared to the antibiotic group (Ant). The same effect was also observed in GOD1200 during days 22–42 and in the 600 U/kg GOD-supplied group (GOD600) when compared to the control group (Ctr). The serum tests indicated that, on day 21, the TGF-β cytokine was significantly decreased in both GOD600 and GOD1200 when compared with Ctr. A decrease in malondialdehyde and an increase in superoxide dismutase in GOD1200 were observed, which is similar to the effects seen in Ant. On day 42, the D-lactate and glutathione peroxidase activity changed remarkably in GOD1200 and surpassed Ant. Furthermore, GOD upregulated the expression of the jejunal barrier genes (MUC-2 and ZO-1) in two phases relative to Ctr. In the aureomycin-supplied group, the secretory immunoglobulin A significantly decreased in the jejunum at 42 days. Changes in microbial genera were also discovered in the cecum by sequencing 16S rRNA genes at 42 days. The biomarkers for GOD supplementation were identified as Colidextribacter, Oscillibacter, Flavonifractor, Oscillospira, and Shuttleworthia. Except for Shuttleworthia, all the abovementioned genera were n-butyrate producers known for imparting their various benefits to broilers. The PICRUSt prediction of microbial communities revealed 11 pathways that were enriched in both the control and GOD-supplied groups. GOD1200 accounted for an increased number of metabolic pathways, demonstrating their potential in aiding nutrient absorption and digestion. In conclusion, a diet containing GOD can be beneficial to broiler health, particularly at a GOD concentration of 1,200 U/kg. The improved feed conversion ratio, immunity, antioxidative capacity, and intestinal condition demonstrated that GOD could be a valuable alternative to antibiotics in broiler breeding.